1986
DOI: 10.1111/j.1440-1827.1986.tb01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Bannayan Syndrome—generalized Lipomatosis Associated With Megalencephaly and Macrodactyly

Abstract: This paper reports an autopsy case of a 5‐year and 11‐month‐old girl with generalized subcutaneous lipomatosis, megalencephaly, and macrodactyly. Marked emaciation and poor prognosis were the characteristic findings of this case. We thought that this case was identical with a rare syndrome which was initially reported by Bannayan in 1971. Autopsy disclosed diffuse lipomatosis in the thoracic and abdominal cavity, and infiltration of fat tissue to the pancreas. Hyperplasia of the small intestinal mucosa and Pey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…A 1986 report by Okumura et al describes a fiveyear-old girl with a phenotype virtually identical to the one reported by Bannayan 15 years earlier [Okumura et al, 1986]. The lipomatosis was extremely aggressive, involving the pleural and abdominal cavities, the former covered with thick sheets of tumor.…”
Section: Bannayan Riley Zonana Ruvalcaba and Related Observationsmentioning
confidence: 86%
“…A 1986 report by Okumura et al describes a fiveyear-old girl with a phenotype virtually identical to the one reported by Bannayan 15 years earlier [Okumura et al, 1986]. The lipomatosis was extremely aggressive, involving the pleural and abdominal cavities, the former covered with thick sheets of tumor.…”
Section: Bannayan Riley Zonana Ruvalcaba and Related Observationsmentioning
confidence: 86%
“…Examples of this uncommon lesion are reported in the literature as only a handful of individual case reports. 121 Associations with rare childhood syndromes such as Shwachman-Diamond, 12,19 Bannayan, 20 or Johanson-Blizzard 13 have been made. Lipomatous pseudohypertrophy often forms a benign mass mimicking cancer, resulting in unnecessary resection and morbidity.…”
mentioning
confidence: 99%
“…The soft tissue and visceral tumours can be present at birth or appear in the first years of life. Their evolution is variable and foreseeable with difficulty: they can grow to become lifethreatening (four deaths reported), remain stable in size, or decrease spontaneously (2)(3)(4)(8)(9)(10). As far as the treatment is concerned, self limiting tumours without symptoms can be treated conservatively otherwise they should be surgically excised.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently Zonana et al found the association in a father and in his two sons, and suggested that the condition was inherited as an autosomal dominant trait (13). Since then, few cases of this rare syndrome, included five sporadic ones, have been reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We present a 7 year old child with the syndrome and mental retardation in whom multiple lipomas were treated with suction-assisted lipectomy.…”
mentioning
confidence: 97%